RELIGIUS MODERATES THE INFLUENCE OF TAX INFORMATION TECHNOLOGY, FRAUD DETECTION, MONEY ETHICS, AND TAX SANCTIONS FOR TAX EVASION - Soedarman, Moh; Restya Clarita Ladjar; Triana Murtingtyas (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
This research aims to analyze the influence of tax information technology, fraud detection, money ethics, and tax sanctions on tax evasion practices, with religiosity as a moderating variable. The population in this study were individual taxpayers registered at KPP Pratama Atambua with a total of 44,000. By using simple random sampling (Simple Random Sampling Technique) because the sampling of sample members from the population was carried out randomly without paying attention to the strata which were assumed to represent the entire population in the population, a sample of 100 people was obtained. The research results show that tax information technology, fraud detection, money ethics, and tax sanctions have a significant effect on tax evasion. The religiosity variable is unable to moderate the influence of tax information technology, fraud detection, money ethics and tax sanctions on tax evasion